Preparation and Applications of Superparamagnetic Iron Oxide Nanoparticles in Novel Drug Delivery Systems: An Overview - Hooshmand, Sara; Hayat, Seyed M. G.; Ghorbani, Ahmad; Khatami, Mehrdad; Pakravanan, Kimya; Darroudi, Majid (Current Medicinal Chemistry, 2021)
Nanocarriers, as drug delivery frameworks, have been intended to enhance the pharmacological and restorative properties of traditional medications. The consolidation of medical atoms as nanocarriers can function as the drug that is required against corruption, as well as offer the desired potential outcomes in regards to targeting and controlled discharge. In the present overview article, applications of magnetic nanoparticles (MNPs) in medication conveyance are outlined. The MNPs have increased the excitement due to their biocompatibility - low poisonous quality, and their capacity to be handled in a magnetic field, which enables their applications as drug-bearing vehicles. The simplicity of surface modification of these particles can provide opportunities for targeting the moieties that are linked to the particle surface. We trust that the intriguing particles will gain further attention alongside achievements in the current ones in the near future.
Keywords: functionalization